2019
DOI: 10.18633/biotecnia.v22i1.1191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Extraction, Chemical Modification and Extrusion of Triticale Starch (Triticosecale) in its Functional Properties//Efecto de la Extracción, Modificación Química y Extrusión de Almidón de Triticale (Triticosecale) en sus Propiedades Funcionales

Abstract: Natural starch (NS) was isolated from triticale flour (TF) and later modified by extrusion (MS) using acetic anhydride as a reactive agent. From each product (NS, TF, MS) a proximal analysis was performed as well as the characterization of its physicochemical properties (particle size determination (PSD), water absorption index (WAI) and solubility index (WSI), color L*, a*, b*, and viscosity), degree of substitution (DS), and thermal properties (differential scanning calorimetry (DSC). Particle below sizes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…These researchers report that the difference was due to starch washes during and after acetylation. The tendency to decrease the protein observed in the different works is influenced by the extrusion process that can generate protein breakdown (denaturation), which impacts and decreases its functional properties [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers report that the difference was due to starch washes during and after acetylation. The tendency to decrease the protein observed in the different works is influenced by the extrusion process that can generate protein breakdown (denaturation), which impacts and decreases its functional properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the work of Vargas [9], where values of 30% in native potato starch and 0.17% in acetylated potato starch were obtained, presenting the same tendency as in this work. During the extrusion process, the fats undergo an emulsion process due to the pressure to which they are subjected as they are covered by the starches and proteins, causing an encapsulation of the fat, so the traditional determination of the ethereal extract will not show the actual results corresponding to product [8]. The above can explain the reason for the decrease in fat in the starches analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Although there are recent reports of the thermal characterization of triticale starch by differential scanning calorimeter and hybrid rheometer, those studies only reached gelatinization temperatures (∼60 °C), and by TGA/DTG the thermal decomposition of triticale straw was reported, however, the straw contains polymeric mixtures and diverse biomass of low molecular weight that allowed higher heat resistance (200−400 °C) and E a (176.1−213.6 kJ/mol). 20,36,37 Synthesis, Morphology, and Physicochemical and Rheological Characterization of Anionic Hydrogels Based on Triticale Starch. Synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been reported that the first stage of pyrolysis is due to chain depolymerization, followed by ring decomposition and carbonization as the final degradation process. The increase in amylose promotes thermal degradation, so the initial drop in weight was due to catalytic depolymerization of the α-1,4 bond, starting with the lowest molecular weight chains. , Although there are recent reports of the thermal characterization of triticale starch by differential scanning calorimeter and hybrid rheometer, those studies only reached gelatinization temperatures (∼60 °C), and by TGA/DTG the thermal decomposition of triticale straw was reported, however, the straw contains polymeric mixtures and diverse biomass of low molecular weight that allowed higher heat resistance (200–400 °C) and E a (176.1–213.6 kJ/mol). ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation